FAKTOR PENYEBAB ORANG DEWASA AWAL MENUNDA PERNIKAHAN DI DESA MARUNGGI KECAMATAN PARIAMAN SELATAN - Oktaviani, Nini - (Bimbingan dan Konseling, 2014)
The background of this research is about there are so many pra adult people who delayed their married, However, in our religion, married is a circumcision from our prophet which have so many benefit for pra adult people. Purpose of this research is to know the factor cause pra adult people delay their married. This research is descriptif kualitatif research. Informan is three pra adult people and the support informan are six people: three mothers and three sisters of pra adult in marunggi village kecamatan pariaman selatan. Data of this research was collected by interview. Goal of the data test by used data triangulasi, from the data analyse by interactive model among of collect data, data reduksi, presentasion and make conclusion.the result of research find out that it this caused pra adult people delay meried are: often faluare loking for partner not research maturity age which infact, rarely has opportunity to meed by commensurable opposite gender, higt indentify by parent, egosentrism and narsism to much season install from cultures of individualism because has duty and family, trauma of broken home and the fat is in the fire think of carrier.